Exploring the Impact of Reflective Learning in Teaching Basic Music Theory: A Qualitative Study - Dedy Setyawan; Juju Masunah; Rita Milyartini; Yudi Sukmayadi (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study investigates challenges in the basic music theory course within the Music Education Study Program at STKIP Citra Bakti, focusing on identifying key learning issues and analyzing student reflections on the course experience. A descriptive approach with a survey method was employed. Data collection included questionnaires and interviews, and analysis was conducted using Miles and Huberman's model, which involves data reduction, data presentation, and data verification. The findings categorize the primary challenges in basic music theory learning into eight areas: (1) Student Characteristics, (2) Learning Attitudes, (3) Motivation, (4) Media/Teaching Materials, (5) Instructor Influence, (6) Family Support, (7) Social Environment, and (8) Infrastructure. Notably, 93.3% of students cited media and teaching materials as a significant issue, while 90% pointed to inadequate infrastructure as a key barrier to effective learning. The analysis highlights a critical need to improve media and teaching materials, as well as infrastructure, to enhance learning experiences. Addressing these issues may foster better engagement and understanding in basic music theory. The study underscores the importance of prioritizing resource allocation for teaching materials and facilities in the Music Education program. Future research should explore strategies to strengthen student interaction with learning materials and promote collaboration between educational institutions and resource providers to support music theory education effectively.